Nulla dies sine linea : research by drawing in the teaching of theory of architecture - Fernandes, Eduardo Jorge Cabral dos Santos (2014)
"Nulla dies sine linea" (no day without drawing a line) is a dictum of Viollet-le Duc that Fernando Távora quoted, regarding the education of students of architecture. Being undisputed for Architectural Design classes, it is equally valid for the teaching of Theory of Architecture. Understanding the role of the architect in a Vitruvian philosophy, as a specialist generalist (a technician/artist who knows how to relate with other technicians and other artists), implies an idea of comprehensive education (not specialized) of the architecture student, so that he can become a professional who, by the scope of his training, can organize the synthesis of all the elements that have to converge in the process of architectural design. Drawing, understood as the ability to create and manipulate images that express ideas, is an instrument that allows us (in conjunction with writing) to relate different areas of knowledge, and should be taught as a tool for interdisciplinary research, both in the Studio classes and in theoretical units. Architecture students should be taught to use images as tools for interdisciplinary research, but this research by drawing should not be confused with mere representation: the consideration of the concepts implied should always be a criterion for the evaluation of the images produced. This kind of work takes place in the Design classes, but can also be developed in the teaching of Theory, where students can develop analytical research as a support for the communication of ideas. This paper will show examples of the work done in classes of Theory and History of Architecture, where students articulate the study of different themes (physical and cultural context, geometry, function, tectonics, etc.) and where the relationship between text and image (drawings, photos and diagrams) is crucial for the communication of ideas.